PERSEPSI REMAJA TERHADAP KONTEN PORNOGRAFI DI MEDIA SOSIAL YOUTUBE - Nurmawati Nurmawati; Daryanti Daryanti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine adolescent perceptions of pornographic content on YouTube social media. The background is that some of them have positive perceptions of pornographic content and some have negative perceptions of pornographic content. This study uses a descriptive method with a quantitative approach. The sampling technique used in this study used a simple random sampling technique by taking samples through the Google from instrument with a Likert scale. The results of this study are that adolescents who have positive and negative perceptions of pornographic content have balanced values.